The Motive of The Suicide: A Forensic Linguistic Study - Marpaung, Magdalena; Indrawati, Ni Luh Ketut Mas; Suparwa, I Nyoman; Malini, Ni Luh Nyoman Seri (Randwick International of Social Science Journal, 2025)
ABSTRACT This study investigates the message of a person who committed suicide in a letter that was found on 7th September 2021. To define the messages in the letter, this study observed the realization of the theme and rheme types and structure. So, there are three focuses of this study; (1) how is the realization of theme and rheme in the letter, (2) how is the structure of the theme and rheme in the letter, and (3) what are the messages the person who committed suicide wanted the readers to know. The analysis defined three findings. First, most of the themes are in the type of single-ideational which explains the confession of the writer because the theory of ideational theme explains it as a theme for a statement or declarative mode of clause. In this first finding, the writer was identified as well-committed in his action of doing suicide. Second, all the themes from each clause are linked in a Constant thematic pattern. This second finding explains the cohesion of the ideas of the writer in his writings. Third, the statement of the writer which was indicated by the single ideational theme and the message unity which was explained the by finding of the constant thematic progression pattern explained 4 messages (1) a giving responsibility of his children to his wife, (2) complains about his wife disrespect to him, (3) a farewell to his children, and (4) a confirmation of his authorship in the letter. The messages which are defined in the letter tell that the motive of the suicide is “a long-term marriage conflict”.